(3GdJHUQI hGdJPcQIs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s
(3ChdgG (B:s
(3jHOC GdehLhO ajg Hbhdg (B: (3hLRe GHf MfHd HGdRgOi (B: (3Yf SGde Ci Yf CHjg GdHQ hPgH CMeO Hf MfHd hcPdc ESMb Hf hGghjI Edi Cf CUM GdCSGfjO eG QhGg CHh HcQ eMeO Hf eSde YHjO Gddg Hf YHO Gddg Hf TgGH Yf SGde Hf YHO Gddg Hf YeQ Yf CHjg s
(3BNQgG (B:s
(3jfJgi GdehLhO ajg CKfGA PcQ eYQaI ef GNJdW ef GdKbGJ Hbhdg (B: (3hai GdKbGJ ef CNjQkG ENJdW aeG Qhi ajg Ch CHge SbW fMh YWG hgh GHf GdSGjH hcGdLQjQi SYjO hCHi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG JUMjMGJs
(3cJHJ GdYfGhjjf HGdMeQI s
(3YdjgG JedcGJ MOjKI s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdMOjK h GdeUWdMs